2022
DOI: 10.1017/s1355617721001466
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early-Life Adversities on Neuropsychiatric and Executive Functions in HIV-Positive Adults

Abstract: Objective: Adverse childhood experiences (ACEs) contribute to elevations in neuropsychiatric and neurocognitive symptoms in HIV+ adults. Emerging data suggest that exposures to threat-related and deprivation-related ACEs may have differential impacts on function, with threat exposure contributing to neuropsychiatric symptoms, and deprivation contributing to executive dysfunction. Yet, it remains unclear how specific types of ACEs impact neuropsychiatric and neurocognitive symptoms in HIV+ adults. Hence, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 90 publications
1
5
0
Order By: Relevance
“… 12 These results are also supported by a case-control study among adults with HIV. 15 The present study further extends the findings of previous research by demonstrating the long-term association of deprivation-related ACEs, but not threat-related ACEs, with the rate of annual cognitive decline in later life. These findings may provide insight into early identification of the vulnerable group and prioritization of interventions for individuals with experience of childhood deprivation to preserve their cognitive function.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“… 12 These results are also supported by a case-control study among adults with HIV. 15 The present study further extends the findings of previous research by demonstrating the long-term association of deprivation-related ACEs, but not threat-related ACEs, with the rate of annual cognitive decline in later life. These findings may provide insight into early identification of the vulnerable group and prioritization of interventions for individuals with experience of childhood deprivation to preserve their cognitive function.…”
Section: Discussionsupporting
confidence: 87%
“…Although the association of ACEs with cognitive function has been consistently reported in different cultural contexts, 6 , 7 , 8 , 9 , 15 few studies have investigated the independent role of threat-related and deprivation-related ACEs on later-life cognitive decline in the general population. A cross-sectional study in the US has shown that childhood deprivation, but not threat, was associated with poor cognitive control in adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several factors are known to contribute to the risk of cognitive impairment in adults living with HIV, including diabetes, hepatitis C virus (HCV) coinfection, and alcohol/substance misuse (e.g., Heaton et al, 2010 ). Emerging data indicate that psychosocial risk factors, such as early-life stress (ELS), also contribute to cognitive impairment among PLWH ( Clark et al, 2012 , 2017 , 2023 ; Spies et al, 2012 , 2016 , 2017 ). High ELS exposure is associated with cognitive impairment among non-HIV samples ( Philip et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%